Criminology and genetically modified food - Walters, Reece (2006)
About the book: In little more than a decade, Green Criminology has become an established new perspective in the field. It embraces an exciting and wide range of topics, from controversies about genetic modification through corporate offending against the environment and human communities, to animal abuse. Green Criminology provides a focal point for longstanding and new areas of research as well as making important interdisciplinary connections